Chromatin enrichment of histone marks H4Ac and H3K9me3 in TP53 gene domain in breast cells - Santos, G.C.Jr; Goes, A.C.S.; de Moura Gallo, C.V. (Вiopolymers and Cell, 2014)
In non-cancerous breast cell lines HB2 and MCF10A the TP53 gene is localized inside a relatively small ~ 50 kb loop domain delimited by two S/MARs. Aim. To analyze the chromatin markers H4Ac and H3K9me3 of these two S/MARs and of the TP53 gene P1 promoter in different breast cells lines. Methods. We used chromatin immunoprecipitation (ChIP) to characterize the chromatin status of these S/MARs elements in breast non-cancerous cell lines HB2 and MCF10A and cancerous MCF-7, MDA-MB-231, BT-474 and T47D cell lines, by chromatin enrichment of H4Ac and H3K9me3 epigenetic markers, hallmarks of open and closed chromatin, respectively. Results. We found that these chromatin epigenetic markers are differentially distributed in S/MARs for all analyzed breast cell lines. Conclusions. We found no correlation between S/MARs and chromatin epige- netic status, suggesting that nuclear matrix fixation and chromatin status can be independent. High enrichment of H3K9me3 in the TP53 gene P1 promoter region in MCF-7, could explain lower levels of the TP53 expression, described earlier by our group. У неонкогенних клітинних лініях HB2 і MCF10A ген TP53 локалізований всередині відносно невеликої області (~ 50 тис. пар нуклеотидів) петлі домену, обмеженої двома S/MARs (ділянками, асо- ційованими з матриксом). Мета. Проаналізувати хроматинові маркери H4Ac і H3K9me3 в означених S/MARs і P1 промоторі гена TP53 в різних клітинних лініях молочної залози. Методи. Використано імунопреципітацію хроматину (чип) для характеристики стану хроматину елементів S/MARs у неонкогенних клітинних лініях HB2 і MCF10A та злоякісних клітинних лініях MCF-7, MDA-MB-231, БТ-474 і T47D за допомогою H4Ac і H3K9me3 епігенетичних маркерів за ознаками відкритого і закритого хроматину відповідно. Результати. Виявлено, що зазначені епігенетичні маркери нерівномірно розподілені в S/MARs для всіх проаналізованих клітинних ліній молочної залози. Висновки. Не знайдено кореляції в епігенетичному статусі S/MARs і хроматина, що дозволяє зробити припущення, що фіксація ядерного матриксу і статус хроматину можуть бути незалежними. Суттєве збагачення H3K9me3 P1 промоторної областігена TP53 в клітинній лінії MCF-7 може бути причиною нижчих рівнів експресії TP53, описаних раніше нашою групою. В неонкогенных клеточных линиях HB2 и MCF10A ген TP53 расположен внутри петли домена:относительно небольшой области (~ 50 тыс. пар нуклеотидов), ограниченной двумя S/MARs (участками, ассоциированными с матриксом). Цель. Проанализировать маркеры хроматина H4Ac и H3K9me3 в указанных S/MARs и P1 промотре гена TP53 в различных клеточных линиях молочной железы. Методы. Использовали иммунопреципитацию хроматина (чип) для характеристики состояния хроматина элементов S/MARs в неонкогенных клеточных линиях HB2 и MCF10A и злокачественных клеточных линиях MCF-7, MDA-MB-231, БТ-474 и T47D с помощью H4Ac и H3K9me3 эпигенетических маркеров по признакам открытого и закрытого хроматина соответственно. Результаты. Указанные эпигенетические маркеры неравномерно распределены в исследованных S/MARs для всех анализируемых линий клеток молочной железы. Выводы. Не выявлена корреляция в эпигенетическом статусе S/MARs и хроматина, что позволяет предположить, что фиксация в ядерного матрикса и статус хроматина могут быть независимыми. Существенное обогащение H3K9me3 P1 промоторной области гена TP53 клеточной линии MCF-7 может быть причиной более низких уровней экспрессии TP53, описанных ранее нашей группой.